Psychological Factors Affecting The Formation of Destructive Behavior in Adolescents - Ismatova Khalavat Bakhtiyarovna (Jurnal Psikologi, 2025)
In this article, the role and significance of psychological factors in the emergence of destructive behavior among adolescents are studied. Within the framework of the study, such key factors as the family environment, peer pressure, emotional stability, the ability for emotional control, and social adaptation were analyzed. The obtained results show that a lack of family support, the influence of negative peers, and problems in emotional management exacerbate the aggressive and aggressive behavior of adolescents. The research results are important in the development of comprehensive measures to prevent destructive behavior in the pedagogical and psychological spheres